Nucleolar protein 6 promotes cell proliferation and acts as a potential novel prognostic marker for hepatocellular carcinoma - Lei Meng (Wolters Kluwer, 2021)
Abstract. Background:. Nucleolar protein 6 (NOL6) is a nucleolar RNA-associated protein that is highly conserved between species. It has been proved to be associated with the prognosis of liver cancer. However, the underlying mechanism has not been fully established. This study aimed to assess the relationship between NOL6 and liver cancer prognosis. Methods:. We constructed an NOL6-short hairpin RNA (shRNA)-expressing lentivirus. Through viral transfection, cell growth assay and fluorescence-activated cell sorting, we evaluated the effect of shRNA-mediated NOL6 knockdown on the proliferation, colony formation, and apoptosis of hepatocellular carcinoma (HCC) cells. The relationship between NOL6 expression and HCC patient survival has been established through bioinformatics analysis. We also explored the downstream molecular regulatory network of NOL6 in HCC by performing an Ingenuity Pathway Analysis in the database. Results:. Increased NOL6 expression was detected in HCC cells compared to normal controls; HCC patients with high NOL6 expression had poorer prognoses than those with low expression. NOL6 knockdown inhibited HCC cell proliferation, apoptosis, and colony formation. Also, MAPK8, CEBPA, and FOSL1 were selected as potential downstream genes of NOL6. Conclusions:. NOL6 up-regulates HCC cell proliferation and affects downstream expression of related genes. Moreover, NOL6 is considered to be associated with poor prognosis in HCC patients.